Internet trade and threat of the grey area - Ćwiąkała-Małys, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
In recent years it has been of great interest to tax, fiscal and customs authorities how trade and services provided over the Internet develop. A long time ago it was stated that the intense development of the Internet contributes to the expansion of the grey area. The grey area’s functioning is very unfavourable to the state economy, because although it creates GDP, it does not directly support the state budget. When considering reduced inflows to the state budget and increases in the deficit, it is reasonable to take any and all actions in order to limit the grey area in each field of social and economic life. Thus, the interest of specialized public authorities in this field should not raise any concerns.
Keywords: szara strefa; Internet; gospodarka państwa; budżet państwa